The role of administrative capacity for an effective implementation of EU cohesion policy - Julia Bachtrögler (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This reflection paper examines the influence of administrative capacity on the absorption and effective use of Cohesion Policy funds. First, it examines the current level of absorption of Cohesion Policy funds in the 2014-2020 programming period. Second, a literature review on the relationship between administrative capacity and the absorption of Cohesion Policy funds highlights the factors affecting the availability of administrative resources. Third, the role of administrative capacity for the effectiveness of funds usage in EU regions is discussed. The literature concludes that the effects of Cohesion Policy are heterogeneous across regions. Administrative capacity is an important element of a region's absorptive capacity, also due to the project selection process through managing authorities. Therefore, measures should be taken to attract motivated and well-qualified staff and to ensure communication and coordination with stakeholders and other relevant bodies. Finally, a recent study on regional development opportunities of green and digital technologies is presented, pointing to the knowledge of administrative staff about regional characteristics and capabilities as essential contribution to "good" policy implementation
Keywords: H83; H87; R58; 330; EU budget; cohesion policy; administrative capacity; absorption; regional policy implementation